Study of camelpox virus pathogenesis in athymic nude mice. - Sophie Duraffour (Public Library of Science (PLoS), 2011)
Camelpox virus (CMLV) is the closest known orthopoxvirus genetically related to variola virus. So far, CMLV was restricted to camelids but, recently, three human cases of camelpox have been described in India, highlighting the need to pursue research on its pathogenesis, which has been hampered by the lack of small animal models. Here, we confirm that NMRI immunocompetent mice are resistant to intranasal (i.n.) CMLV infection. However, we demonstrate that CMLV induced a severe disease following i.n. challenge of athymic nude mice, which was accompanied with a failure in gaining weight, leading to euthanasia of the animals. On the other hand, intracutaneous (i.c.) infection resulted in disease development without impacting the body weight evolution. CMLV replication in tissues and body fluids was confirmed in the two models. We further analyzed innate immune and B cell responses induced in the spleen and draining lymph nodes after exposure to CMLV. In both models, strong increases in CD11b(+)F4/80(+) macrophages were seen in the spleen, while neutrophils, NK and B cell responses varied between the routes of infection. In the lymph nodes, the magnitude of CD11c(+)CD8α(+) lymphoid and CD11c(+)CD11b(+) myeloid dendritic cell responses increased in i.n. challenged animals. Analysis of cytokine profiles revealed significant increases of interleukin (IL)-6 and IL-18 in the sera of infected animals, while those of other cytokines were similar to uninfected controls. The efficacy of two antivirals (cidofovir or HPMPC, and its 2, 6-diaminopurine analog) was evaluated in both models. HPMPC was the most effective molecule affording 100% protection from morbidity. It appeared that both treatments did not affect immune cell responses or cytokine expression. In conclusion, we demonstrated that immunodeficient mice are permissive for CMLV propagation. These results provide a basis for studying the pathogenesis of CMLV, as well as for evaluating potential antiviral therapies in an immunodeficiency context.